A new suture technique for anastomosis in radical retropubic prostatectomy and early removal of urethral catheter. - (:unkn) unknown (My University, 2007)
INTRODUCTION: A modified suture technique for urethro-vesical anastomosis during radical retropubic prostatectomy was developed and utilized in a cohort of patients. Comparative analysis of postoperative outcome was performed with a previous group of patients who had an anastomosis with the conventional technique. MATERIAL AND METHODS: A consecutive group of patients who underwent radical retropubic prostatectomy in our department with the diagnosis of localized prostate cancer was included in this retrospective study. Urethro-vesical anastomosis was performed either with the new or conventional method (CM). Outcome data of these two different patient sets were compared. RESULTS: One-hundred and one consecutive patients (mean age of 61.9 years) who were operated by either one of the two anastomotic suture techniques composed our study group. The mean follow-up period was 18 months (min: 12-max: 24). Urethro-vesical "U" (UVU) suture was performed in 51 patients, and CM in 50 patients. Foley catheter was removed at postoperative fourth day in 33 (64.7%) and 18 (36%) patients in UVU and CM groups, respectively (p < 0.01). Incontinence rate was significantly lower in the UVU group at postoperative first year (p < 0.0005). Anastomotic strictures were observed in only 1.9% of the cases in UVU group, compared to 4% in CM group. CONCLUSION: Outcome data from our patient group indicate that UVU suture may allow a high quality urethro-vesical anastomosis with a very favorable outcome in terms of early catheter removal, high continence and low stricture formation rates in patients undergoing radical retropubic prostatectomy. Further validation of these results requires a prospective randomized trial.